Strategi Komunikasi Public Relations KSBI Jagakarsa (Komunitas Sukses Berjamaah Indonesia) dalam Menyikapi Program Makan Gratis Pemerintahan Prabowo - Syailendra Reza Irwansyah Rezeki (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This article aims to analyze the public relations (PR) communication strategy of Komunitas Sukses Berjamaah Indonesia (KSBI), a community-based Micro, Small and Medium Enterprises (MSMEs) organization in Jagakarsa, in responding to the free meal program initiated by the Prabowo administration. Descriptive qualitative research with a situational analysis approach and literature study explores how KSBI can utilize the PR function to respond to economic participation opportunities and build a positive image amidst the implementation of the national-scale program. The results of the study indicate that the PR strategy implemented by KSBI is centered on five main elements: (1) message management that emphasizes the potential contribution of local MSMEs in providing quality and sustainable products for the program and its impact on community economic empowerment; (2) prioritizing direct dialogue with local governments and related agencies, active participation in MSME forums and utilizing local and social media to reach stakeholders; (3) proactive communication strategy through partnership offers, demonstrations of members' production capacity and internal education regarding participation opportunities; (4) reactive and responsive communication strategy to information on procurement opportunities and potential obstacles to MSME participation; and (5) Building a local economic empowerment narrative that consistently highlights the benefits of MSME involvement in programs for the community in Jagakarsa. Conclusion, that KSBI faces the urgency to adopt an adaptive and collaborative PR strategy, which not only focuses on promoting member potential but also building strong good relationships with the government and other stakeholders. By communicating the unique value of local MSMEs and the potential synergy with the free meal program, KSBI can maximize economic participation opportunities, increase community visibility and contribute significantly to the success of the program while empowering members.